Surgical treatment for ruptured dural arteriovenous fistula with large intracranial hematoma - Ye, Xianwang (Int J Clin Exp Med, 2014)
The rupture of dural arteriovenous fistula (DAVF) is a serious complication endangering the lives of patients. It is difficult to treat such ruptured DAVF with large intracranial hematoma since lacking of early diagnostic methods. Meanwhile, there was no consensus of how to surgically treat these patients in early stage. In this study, we tried to use 4D-CTA to diagnose DAVF and guide surgical treatment. Based on the result of 4D-CTA, we attempted to eliminate DAVF at the same time we removed hematoma. The result was encouraging. 7 patients with ruptured DAVF presented as large spontaneous intracranial hemorrhage were included in this research between May, 2010 and August, 2012 in our hospital. 4D-CTA was performed in all cases. All results of 4D-CTA inspections were studied by both neurosurgeon and neuroradiologist. The therapeutic options were evaluated based on the clinical and angiographic results. All fistulas of seven patients were eliminated at the same time the hematoma being evacuated. 4D-CTA was sufficient for detecting and recognizing basic vessel angioarchitecture of DAVF to guide surgical treatment. Main arterial supplies, fistula location and CVDs found during surgery are consistent with the results 4D-CTA. All seven cases achieved completely fistula occlusion in operation without new neurological complication. We favor one stage surgical treatment for ruptured DAVF with large intracranial hemorrhage. 4D-CTA plays an important role in preoperative emergent inspection for its safety, rapidity and accuracy. However, it still needs further and larger investigations to optimize such treatment methods and to find out other potential risks.